Lean hospitals : improving quality, patient safety, and employee engagement, second edition - Graban, Mark (CRC Press, 2012)
"The new edition of this Shingo Prize-winning international bestseller lays out a framework for defining and understanding Lean hospitals. It starts off by examining the challenges faced by hospitals, including rising costs, falling reimbursement rates, employee retention, and patient safety and satisfaction. Full of examples and case studies, the second edition has been updated to reflect current pressures on hospitals, including the Affordable Care Act, and includes new and updated case studies. New material includes discussions on process audits, performance measures and suggestion management as well as a new chapter on strategy deployment"--Provided by publisher.